Amino‐functionalised mesoporous silica microspheres for immobilisation of Candida antarctica lipase B – application towards greener production of 2, 5‐furandicarboxylic acid. Issue 8 (29th September 2020) - Saikia, Kongkona; Senthil Kumar, Ponnusamy; Karanam Rathankumar, Abiram; SaiLavanyaa, Sundar; Srinivasan, Lakshmi; Subramanian, Sivanesan; Cabana, Hubert; Gosselin, Mathilde; Vinoth Kumar, Vaidyanathan
Abstract : In the present study, amino‐functionalised mesoporous silica microspheres were utilised as support for the covalent immobilisation of Candida antarctica lipase B (CaLB) for the subsequent production of 2, 5‐furandicarboxylic acid (FDCA) from 2, 5‐diformylfuran (DFF). Under the optimised operating conditions of pH 6.5, particle/enzyme ratio of 1.25:1.0 and glutaraldehyde concentration of 4 mM, a maximum CaLB immobilisation yield of 82.4% on silica microspheres was obtained in 12.25 h. The immobilised CaLB was used for the synthesis of alkyl esters, which were utilised along with hydrogen peroxide for FDCA synthesis. The biocatalytic conversion of 30 mM DFF dictated a 77–79% FDCA in 48 h at 30°C; where the turnover number and turnover frequency of immobilised CaLB were 6220.73 mol mol −1 and 129.59 h −1, respectively, for ethyl acetate, against 6297.65 mol mol −1 and 131.2 h −1, respectively, for ethyl butyrate. Upon examining the operational stability, the immobilised CaLB exhibited high stability till five cycles of FDCA production.